2018
DOI: 10.1093/cid/ciy669
|View full text |Cite
|
Sign up to set email alerts
|

How Clean Is the Linen at My Hospital? The Mucorales on Unclean Linen Discovery Study of Large United States Transplant and Cancer Centers

Abstract: Mucormycosis outbreaks have been linked to contaminated linen. We performed fungal cultures on freshly-laundered linens at 15 transplant and cancer hospitals. At 33% of hospitals, the linens were visibly unclean. At 20%, Mucorales were recovered from >10% of linens. Studies are needed to understand the clinical significance of our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Some other cases occurred in cluster and were linked to the use of contaminated devices (such as adhesive bandages, wooden tongue depressors, ostomy bags) or environmental reservoir (water circuitry and adjacent building construction) [31]. Recent outbreaks have been linked to contaminated hospital linens [34,35,36]. Skin was the most common localization (57%), followed by gastrointestinal tract (15%) in HCM [31].…”
Section: Health-care Associated Mucormycosis (Hcm)mentioning
confidence: 99%
“…Some other cases occurred in cluster and were linked to the use of contaminated devices (such as adhesive bandages, wooden tongue depressors, ostomy bags) or environmental reservoir (water circuitry and adjacent building construction) [31]. Recent outbreaks have been linked to contaminated hospital linens [34,35,36]. Skin was the most common localization (57%), followed by gastrointestinal tract (15%) in HCM [31].…”
Section: Health-care Associated Mucormycosis (Hcm)mentioning
confidence: 99%
“…Recently, a number of outbreaks were linked to contaminated hospital linens or laundry carts and bins [35][36][37][38]. The full extent to which contaminated linens contribute to the burden of hospital-acquired mucormycosis is unknown and may be under-appreciated.…”
Section: Hospital Environmentsmentioning
confidence: 99%
“…Moreover, it is unknown whether contaminated linens account for sporadic cases of mucormycosis. Sundermann and colleagues performed fungal cultures on freshly laundered linens at 15 transplant and cancer hospitals [38]. At 33% of hospitals the lines were visibly unclean.…”
Section: Hospital Environmentsmentioning
confidence: 99%
“…In response to a mucormycosis outbreak where linens were one suspected source, investigators conducted an audit of 15 transplant and cancer hospitals and found seven (47%) centers had freshly laundered healthcare linens contaminated with mucormycetes. Three (20%) of the 15 centers failed to meet hygienically clean standards for mucormycetes [95]. In total, 14% of healthcare linens were found to have mucormycetes.…”
Section: Components Of An Outbreak Investigationmentioning
confidence: 99%